Investigation of Bacteremia due to Aeromonas Species and Comparison with That due to Enterobacteria in Patients with Liver Cirrhosis. (29th December 2011) - Shizuma, Toru; Tanaka, Chiharu; Mori, Hidezo; Fukuyama, Naoto
Abstract : Background . The role of Aeromonas species (sp.) in bacteremia in Japanese patients with liver cirrhosis is poorly understood. Aim . To establish the importance of Aeromonas sp. as a cause of bacteremia in patients with liver cirrhosis. Methods . Clinical and serological features and short-term prognosis were retrospectively investigated and compared in Japanese patients with bacteremia due to Aeromonas sp. (n = 11 ) and due to enterobacteria ( E. coli, Klebsiella sp., and Enterobacter sp.) (n = 84 ). Results . There were no significant differences in patients' clinical background, renal dysfunction, or short-term mortality rate between the two groups. However, in the Aeromonas group, the model for end-stage liver disease (MELD) score and Child-Pugh score were significantly higher than in the enterobacteria group. Conclusion . These results indicate that the severity of liver dysfunction in Aeromonas -induced bacteremia is greater than that in enterobacteria-induced bacteremia in Japanese patients with liver cirrhosis.